Outing Class Edukatif untuk Mengenalkan Produk Lokal Indonesia dan Kegiatan Ekonomi pada Siswa Sekolah Dasar - Meitri Purnaningsih; Nasywa Rahma Alya; Iin Purnamasari (STKIP Subang, 2026)
This study aims to describe the implementation of an educational outing class, improve elementary school students’ understanding of economic activities, introduce Indonesian local products, and strengthen Pancasila values through contextual learning. The research employed a descriptive qualitative approach involving third-grade elementary school students. Data were collected through participatory observation, documentation, student worksheets (LKPD), and reflective activities. The outing class was conducted at Warung Wedang Rempah dan Asem Jawa and Home Industry Pia Citra Sari Wangi as learning resources for economic activities and local product recognition. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings revealed that the outing class effectively connected classroom concepts with real-life experiences. Students demonstrated a better understanding of production, distribution, and consumption processes through direct observation and interaction with local entrepreneurs. In addition, students developed greater appreciation and pride toward Indonesian local products and gained awareness of the importance of supporting local businesses. The activity also enhanced students’ learning motivation, participation, critical thinking, and social interaction. Furthermore, values related to Pancasila, such as gratitude, respect for others, cooperation, and love for the homeland, were naturally integrated into the learning process. Therefore, outing class can be considered an effective contextual learning strategy to support the implementation of the Merdeka Curriculum in elementary schools.